Intra-group Interaction in the School Сlass as a Factor of Social Media Addiction Development in Adolescence - Kurliuk, Marianna (Psychological Prospects Journal, 2015)
The article deals with the features of intra-group interaction in the school class as a factor in the formation of social media addiction. The concept of intra-group interaction, its main indicators and manifestations are analyzed. Significant aspects of adolescence, such as: social life, appraisal of others, group membership, authority among the inner circle are shown. For teenagers the role of the inner circle mainly plays a school class in which they spend most of their time. If a teenager is dissatisfied with the interaction in the class, he/she desires to compensate a failure in the real communication with the help of the virtual one that is possible in the social media, and provides new opportunities. The article presents advantages and disadvantages of using social media. The  author comes to a conclusion that the use of social media helps teens to expand the boundaries of communication, facilitates the ability of finding like-minded people and emotional support, gratifies the need of being a part of a group and the need for recognition. However, excessive (pathological) use of the social media can lead to the formation of addiction. It is considered that social media addiction is formed when a teen becomes so obsessed with social media that it distracts him/her from engaging in the real world, and in turn, causes harmful effects on multiple aspects of life.
Keywords: interaction in the group, Internet-addiction, addiction, social mala- djustment, escapism, teenagers